Long-term outcomes of tension-free repair for the primary inguinal hernias - Büyüker, Fatih; Baysal, Hakan; Tosun, Salih (The European Research Journal, 2021)
Objectives: Mesh repair is the gold standard in inguinal hernia (IH) repair. If suture repair is to be performed, the common view is to apply tension-free repair. The aim of our study was to analyze retrospectively the changes in primary IH repair at our clinic in 24-years period with regard to the surgical techniques used, patient demographics, complications, and duration of hospital stay. Methods: The study is based on retrospective analyses of IH repair in 1020 patients in two different periods. In the first period of the study, between 1997-1999 Modified Bassini (MB) method was used for suture repair and Lichtenstein (LH) method was used for mesh repair. In the second period of the study, between 2017-2019, LH method was used for mesh repair and Posterior Wall Darn (PWD) method was used for suture repair. Results: The rates of postoperative complications were high and time to return to work was longer in suture repair with MB. Less postoperative complications, shorter time to return to work and less recurrence were observed in the PWD method compared to MB. Conclusions: Suture repair is a preferable option only in relevant cases and these must be tension free repair techniques such as PWD. When required, suture repairs could be successfully performed with low complication and recurrence rates, similar to mesh repairs by experienced surgical teams.